Design and rationale of the EVOCATION trial: A prospective, randomized, exploratory study comparing the effect of evolocumab on coronary microvascular function after percutaneous coronary intervention in patients with stable coronary artery disease. Issue 1 (January 2022) - Asakura, Masanori; Hibi, Kiyoshi; Shimizu, Wataru; Fujii, Kenshi; Suwa, Satoru; Okumura, Yasuo; Mano, Toshiaki; Igeta, Masataka; Okamoto, Rika; Ishihara, Masaharu
Highlights: Periprocedural myocardial infarction (PMI) remains a common complication of percutaneous coronary intervention. Statin reduces PMI by preventing coronary microvascular dysfunction. We investigate the effect of evolocumab on PMI in stable coronary artery disease patients. Abstract: Percutaneous coronary intervention (PCI) is a standard treatment in patients with stable coronary artery disease (CAD); however, periprocedural myocardial infarction (PMI) remains a common complication of PCI. Aggressive lipid-lowering therapy with statin has shown to reduce the incidence of PMI by preventing coronary microvascular dysfunction. It is unclear whether evolocumab, a potent lipid-lowering agent, could diminish microvascular damage after PCI. The EVOCATION trial (jRCTs051180022) is a multicenter, randomized, open-label, active-controlled, parallel-group, exploratory, investigator-initiated clinical study to evaluate whether pretreatment with evolocumab could decrease the index of microvascular resistance (IMR) after PCI in patients with stable CAD. This study population consists of 100 patients with stable CAD who will undergo PCI and have high low-density lipoprotein cholesterol levels despite administration of maximum tolerated dose of statins for at least 2 weeks. Eligible patients are randomized in a 1:1 ratio to receive either evolocumab 140 mg every 2 weeks in addition to standard of care treatment or standard of care treatment only for 2–6 weeks before PCI. The primary endpoint is IMR after PCI. The EVOCATION trial will evaluate whether pretreatment with evolocumab reduces periprocedural microvascular damage in patients with stable CAD undergoing PCI. Graphical abstract: Image, graphical abstract